“THE MOST USEFUL MEMBER OF SOCIETY?”: AN ANALYSIS ON THE IMPACT OF ENLIGHTENMENT ON ANTI-SLAVERY ARGUMENTATION IN THE LATE 18TH CENTURY AMERICAS - Yang, Andrew Chixiao (PEOPLE: International Journal of Social Sciences, 2019)
This paper focuses on the impact of the Enlightenment movement in Europe and the Americas on how the anti-slavery advocates structured their argumentations and supporting evidence. By mainly examining primary sources in the late eighteenth century, such as local newspapers and lawsuit documents, and comparing it with prior anti-slavery writings as The Selling of Joseph, this paper is able to find evidences of new argumentation methods such as rational thinking and the use of pure reason, as praised by the Enlightenment thinkers. Also, this paper can find traces of existing ideas proposed by well-known Enlightenment thinkers such as John Locke and Thomas Jefferson in the primary sources it examines. The most exciting findings of this paper are how anti-slavery supporters' argument showed traces of early socialists ideas, which is believed by the author to be the product of their use of reason and rational thinking.